2023
DOI: 10.1111/cdev.13998
|View full text |Cite
|
Sign up to set email alerts
|

Configurations of mother–child and father–child attachment relationships as predictors of child language competence: An individual participant data meta‐analysis

Or Dagan,
Carlo Schuengel,
Marije L. Verhage
et al.

Abstract: An individual participant data meta‐analysis was conducted to test pre‐registered hypotheses about how the configuration of attachment relationships to mothers and fathers predicts children's language competence. Data from seven studies (published between 1985 and 2014) including 719 children (Mage: 19.84 months; 51% female; 87% White) were included in the linear mixed effects analyses. Mean language competence scores exceeded the population average across children with different attachment configurations. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 105 publications
2
3
0
Order By: Relevance
“…These findings are moreover consistent with two recent metaanalytic reports (not available at the time of our registration) that infant attachment is associated with academic outcomes (i.e., Dagan et al, 2023;Deneault et al, 2023). More specifically, Deneault and colleagues (2023) found that mother-child attachment, as measured by the Strange Situation Procedure, was metaanalytically associated with the child's cognition (r = .17) and language outcomes (r = .16).…”
Section: Infant Attachment and The Domain Of Academic Competencesupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are moreover consistent with two recent metaanalytic reports (not available at the time of our registration) that infant attachment is associated with academic outcomes (i.e., Dagan et al, 2023;Deneault et al, 2023). More specifically, Deneault and colleagues (2023) found that mother-child attachment, as measured by the Strange Situation Procedure, was metaanalytically associated with the child's cognition (r = .17) and language outcomes (r = .16).…”
Section: Infant Attachment and The Domain Of Academic Competencesupporting
confidence: 91%
“…Importantly, a similar pattern has been observed repeatedly with respect to direct observations of the quality of early caregiving (e.g., maternal sensitivity), such that associations observed between the quality of mother-child interactions in infancy and academic skills is reliably stronger than it is for socioemotional outcomes across several prospective, longitudinal data sets (e.g., Fraley et al, 2013;Haltigan et al, 2013;Raby et al, 2015;Roisman & Fraley, 2012). Nevertheless, due to the relative lack of literature regarding infant attachment and academic skills (but see Dagan et al, 2023;Deneault et al, 2023), it is currently unclear what might be driving these patterns of results. Several hypotheses based on attachment theory have been proposed in earlier work, however (see Bretherton et al, 1979;Van IJzendoorn et al, 1995).…”
Section: Infant Attachment and The Domain Of Academic Competencesupporting
confidence: 66%
“…As has been frequently noted, future studies exploring these distinctions should endeavor to overcome the consistent limitation in the field of attachment of small samples (Cassidy & Berlin, 1994; Deneault, Bureau, et al, 2022; Deneault, Hammond, et al, 2023; Groh et al, 2014; Madigan et al, 2023; Verhage et al, 2016). It is critical, therefore, that future research leverage multisite data collection approaches and/or individual participant data (IPD) analyses when examining distinct antecedents and sequelae of avoidant, resistant, and disorganized attachment (e.g., Dagan et al, 2024; Verhage et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent IPD synthesis on 1,097 dyads from nine studies that had both child–mother and child–father attachment, Dagan et al (2021) demonstrated that the presence of at least one insecure attachment relationship (with either fathers or mothers) versus secure attachment with both parents increased the child’s risk of developing elevated internalizing problems. Studies that include a multiple-caregiver framework that more accurately characterize the social context in which children develop, such as the one by Dagan et al (2024) and one by Van IJzendoorn et al (1992) that included day care providers, have the potential to advance scientific understanding and spur new and novel research directions in developmental science.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, randomized clinical trials appear to support this view, in finding consistent improvements in children's expressive linguistic abilities with increases in child-to-parent interactions [72][73][74][75]. But perhaps most intriguingly, recent meta-analyses have shown that children with secure attachment to both their mother and father have greater language capabilities compared to children with one or no securely attached relationships [76].…”
Section: The Social Brain and First Language Acquisitionmentioning
confidence: 99%